Sentimental Comedy in Martin Amis's "State of England" and "The Coincidence of the Arts" - Verrier, Luc (Miscelánea: A Journal of English and American Studies, 2003)
This article examines the analogies that "State of England" and "The Coincidence of the Arts" -two short stories extracted from Martin Amis's Heavy Water and Other Stories (1998)- bear to the conventions of sentimental comedy in order to shed light on Amis's aesthetic and ethical choices. Relying on tools such as "flyting", these stories comically rework the "pity for the poor" typical of sentimental works while borrowing from the genre of "condition of England" fiction. Yet, this comic veneer cannot conceal the apocalyptic instances of child abuse and domestic violence, topoi of sentimental works. Impending doom is nevertheless undermined by ironic patterns of reconciliation which tally with the cosmic optimism ultimately promoted by sentimental works. Since these denouements are attained via rhetorical negativity, Amis's texts are also indebted to sentimental rhetoric, a heritage that betrays a resurgence of sentimentality in the work of an author wrongfully stereotyped as an effete prophet of doom.
Keywords: Sentimental comedy; Condition-of-England fiction; Flyting; Apocalyptic violence; Agonistic reconciliation